High‐Arsenic Groundwater in the Southwestern Bengal Basin Caused by a Lithologically Controlled Deep Flow System. Issue 22 (29th November 2019) - Khan, M. R.; Michael, H. A.; Nath, B.; Huhmann, B. L.; Harvey, C. F.; Mukherjee, A.; Choudhury, I.; Chakraborty, M.; Ullah, M. S.; Ahmed, K. M.; Goodbred, S. L.; Schlosser, P.; et al.
Abstract: Elevated arsenic in Bengal Basin aquifers threatens human health. Most deep (>150 m) groundwater in Pleistocene aquifers is low in arsenic; however higher concentrations have been reported in the southwest border region. Here, we establish that this extensive arsenic contamination at depth is not associated with well failure. A combination of geochemistry and flow modeling constrains the factors that contribute to arsenic contamination at depth in this region. Deep groundwater in the affected area is younger (2.0 ± 0.6 kyr) than deep, low‐arsenic groundwater elsewhere (12.0 ± 4.0 kyr) based on radiocarbon. Stratigraphic data indicate pre‐Holocene deposition of the contaminated aquifers, but few low‐permeability strata. Numerical modeling indicates that this stratigraphic anomaly permits a natural flow system that transports shallow groundwater to depth. Thus, in areas lacking low‐permeability layers, arsenic contamination can occur in pre‐Holocene aquifers and is probably not an early sign of future deep contamination in regions with interbedded low‐permeability strata. Plain Language Summary: Exposure to arsenic in untreated groundwater pumped from millions of shallow wells across rural South Asia causes life‐threatening cardiovascular disease and cancers in adults and reduces intellectual function in children. Deep (>150 m) groundwater low in arsenic is currently the most effective mitigation option in Bangladesh. This study shows that high concentrations of arsenic observed in deep aquifers in the border area between Bangladesh and India are likely confined to that region due to the absence of clay layers vertically dividing the sandy aquifer. Flow modeling constrained by groundwater dating shows that this contamination is therefore of natural origin and unlikely to expand to wider areas in the near future. Key Points: Groundwater >150 m deep is contaminated with arsenic in a 100‐km‐long latitudinal transect across the southwestern Bengal Basin Radiocarbon ages of deep groundwater are considerably lower in high‐As area compared to the rest of the basin Modeling and analysis indicate that naturally deep flow in sand‐dominated stratigraphy likely causes younger ages and high As concentrations